What's in your list?: A survey of business database holdings and funding sources at top academic institutions. Issue 2 (2nd April 2016) - Kim, Kyunghye; Wyckoff, Trip
ABSTRACT: The present study reports the online business database holdings of the top academic institutions in the United States, which databases are paid for by which entities on campus, and some of the most common and most desired business databases. An invitation to participate in an online survey was sent to 91 top institutions of which 39 institutions participated. The results show a wide variety of information resources are considered core business resources in contemporary business librarianship and imply an increasing importance of cost sharing in providing the databases to support research and efforts to commercialize research.